ENTREPRENEURIAL INTEREST: FINANCIAL LITERACY AND NON-FINANCIAL FACTORS - Himma, Faiqotul; Rosyida, Isnaini Anniswati; Zulkarnaen, Have (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the influence of financial literacy, entrepreneurial knowledge, and Locus of Control on entrepreneurial interest in Generation Z, with Self-efficacy as a moderating variable. The background of this study is based on the important role of the younger generation, especially students, in developing entrepreneurial potential to face future economic challenges. This study uses a quantitative approach with a survey method. The sample in this study were 84 accounting students in Lamongan Regency, selected through a purposive sampling technique. Data were collected using a questionnaire and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results show that entrepreneurial knowledge and Locus of Control have a significant positive effect on entrepreneurial interest. Conversely, financial literacy and self-efficacy do not affect entrepreneurial interest. In addition, Self-efficacy is unable to moderate the relationship between the three independent variables on entrepreneurial interest. This finding underscores the importance of strengthening aspects of knowledge and self-control in shaping entrepreneurial interest, rather than merely financial understanding. The implications of this research are expected to be used as consideration in designing entrepreneurship development programs in higher education environments.